Os neologismos como um processo de resistência : observações linguísticas na comunidade Wakalitesu : aldeia Três Jacus - Camargo, Jonathan de Paula (2020)
Motivated by the scientific curiosity on understanding the ways new words are constituted in a language and how those words and its linguistic functions are related to lexical and semantic constructions by speakers, this work is regarded to neologisms in Wakalitesu Language, which belongs to Nambikwara linguistic family. It is assumed the conception of neologism as a linguistic practice that occurs with the entering or the coining of new words resulting from the need for naming new information, tools and technology which sometimes are not culturally familiar because there was no previous reference in the ethnic language for them. For this study, at first, it was visited researchers that approach neologism formation process, or word creation, as well as their classifications in multiple indigenous languages (DOURADO; PRAÇA, 2016; PRAÇA, 2012; OLIVEIRA; LEAL; MORI, 2014; BORGES, 1998; GONÇALVES, 2007). So it was possible to make the analysis more specifically focused in manifestations of neologisms in Wakalitesu language, we also considered some studies developed in other languages of Nambikwara linguistic family (COSTA, 2020; SOUZA NETTO, 2018; TELLES, 2014, 2013, 2002; PRICE, 1978). The present research has qualitative approach using methodological procedures of field research from which we present some neologism processes in Wakalitesu, highlighting the processes of word creation as linguistic resistance. We expect that the work can contribute to the community current sociolinguistics reality as the ethnic language maintenance and the enhancement of spoken languages diversity in the state of Mato Grosso.